2016
DOI: 10.1093/ntr/ntw238
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke Exposure in Indoor and Outdoor Locations in Airports Across Europe and the United States: A Cross-Sectional Study

Abstract: Airports are known to allow exceptions to smoke-free policy by providing DSRs. We found that smoking still occurs in indoor areas in airports, particularly in the context of DSRs. Smoking, moreover, is widespread in outdoor areas and compliance with smoking restrictions is limited. Advancing smoke-free policy requires improvements to the physical environment of airports, including removal of DSRs and implementation of stricter outdoor smoking restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A separate paper discusses in detail the relationship between the physical environment of airports, including presence of smoking behavior or cues indoor and outdoor (smokers, smelling smoke, cigarette butts, ashtrays), presence of designated smoking rooms, no-smoking signage, and other factors [19]. Among the airports containing designated smoking rooms, two rooms in Europe showed cigarette advertisements (Camel brand logo appeared in Frankfurt and Munich, and the Munich room was called the “Camel Smoking Lounge”).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A separate paper discusses in detail the relationship between the physical environment of airports, including presence of smoking behavior or cues indoor and outdoor (smokers, smelling smoke, cigarette butts, ashtrays), presence of designated smoking rooms, no-smoking signage, and other factors [19]. Among the airports containing designated smoking rooms, two rooms in Europe showed cigarette advertisements (Camel brand logo appeared in Frankfurt and Munich, and the Munich room was called the “Camel Smoking Lounge”).…”
Section: Resultsmentioning
confidence: 99%
“…Findings on the physical environment of airports and exposure to secondhand tobacco smoke in indoor and outdoor locations are presented in a separate manuscript [19], and findings on e-cigarettes observed in airports and during flights are presented in a separate manuscript [20]. The Institutional Review Board at the Johns Hopkins Bloomberg School of Public Health approved all study protocols and materials, and this study did not involve human subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed this parameter because PM2.5, although an important marker of environmental air pollution [29], can be nonspecific as a surrogate for SHS in settings with multiple pollutants [2, 30], and studies have suggested that the vehicular contribution to urban ambient PM2.5 levels can reach the range of 32–40% [31, 32]. One study of tobacco exposure in airports in the United States and Europe explicitly declined to measure PM2.5 levels, citing this lack of specificity, and instead measured air nicotine levels [33]. However, when compared directly in controlled environments, a single cigarette produced over twice as much particulate emissions as two heavy-duty diesel trucks [34], and three cigarettes produced PM levels ten times greater than a single 2.0 litre diesel engine [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite progress in the enactment of comprehensive indoor smoking bans in many localities, outdoor bans have lagged behind, with controversy surrounding both the legality [43] as well as the effectiveness [4446] of such ordinances, even if the hazardous nature of outdoor SHS has now been fully established [47]. Nevertheless, it is being increasingly recognized that “outdoor smoking is an important area for advancing smoke-free policy” [33], and calls for total, premise-wide bans in the airport setting are gaining in traction. Indeed, Article 8 of the World Health Organization's Framework Convention on Tobacco Control (FCTC) demands “universal protection by ensuring that all indoor public places, all indoor workplaces, all public transport and possibly other (outdoor or quasi-outdoor) public places are free from exposure to second-hand tobacco smoke” [48].…”
Section: Discussionmentioning
confidence: 99%